Jørgen Goul Andersen, Peter Munk Christiansen, Torben Beck Jørgensen, Lise Togeby, Signild Vallgårda (red.), Den demokratiske udfordring, København: Reitzels Forlag, 304 s., kr. 225,00. - Klaudi Klausen, Kurt (Politica, 2000)
-